Maslow's and Freud's Theories Reflected in Andrew Laeddis' Character - Friskila Yesika Novelia Hutagaol; Agnes Widyaningrum (Humanitatis : Journal of Language and Literature, 2023)
This research explores the portrayal of schizophrenia symptoms in the character Andrew Laeddis from the movie "Shutter Island". It examines how psychoanalysis and Maslow's hierarchy of needs can be applied to analyze his condition and coping mechanisms. The study aims to understand how Andrew deals with his schizophrenia and fulfils his needs as a person with a mental illness. The research adopts a psychological approach, using Sigmund Freud's psychoanalysis theory and Maslow's hierarchy of needs. This research uses the qualitative descriptive method and content analysis techniques to analyze Andrew's character. The data for analysis and interpretation are derived from the film's script and related theories. The study combines qualitative methods and content analysis to provide a detailed portrayal of Andrew Laeddis' psychological makeup and character traits. The findings reveal that Andrew exhibits symptoms representing the three aspects of Freud's psychological structure: id, ego, and superego. The id is evident in his violent and impulsive behaviour driven by a desire for revenge. The ego is seen in his desire for control and mastery over his mind and body. The superego manifests as his respect for authority and social norms. Additionally, the analysis based on Maslow's theory shows that Andrew's behaviour reflects his struggle to fulfil his basic physiological needs and his higher-level needs for safety, love and belonging, esteem, and self-actualization.